Improving Administrative Skills of Foster Children at Panti Asuhan Muhammadiyah Surabaya through Learning Microsoft Excel - Anindo Saka Fitri; Seftin Fitri Ana Wati; Eristya Maya Safitri (Nusantara Science and Technology Proceedings, 2022)
Along with the development of technology and all the conveniences offered, individual abilities, especially administrative capabilities, must be improved to increase competitiveness. Competitiveness here is competitiveness in the world of work that demands the ability to master administrative capabilities. Panti Asuhan Muhammadiyah Surabaya owns the problem. Lack of funds, facilities, and caregivers or volunteers who can help provide skills training. According to the Ministry of Social Affairs RI 2004, one of the functions of the Orphanage is as a center for skills development (which is a supporting function). Therefore, this educational activity is intended to provide insight for orphanage children in improving administrative capabilities. The purpose of this service program is to provide them with skills they will use in managerial activities in the world of work. This activity was attended by 16 participants offline. This activity aims to make foster children have skills in operating a number processing application (Microsoft Excel). This activity does not only focus on providing material but also on hands-on practice. From the results of the assessment, it was found that 14 children entered Microsoft Excel 2016 Intermediate Skills and 2 children entered Beginner Skills. This training is expected to improve the ability of foster children in administrative capabilities using Ms. Excel and can apply the knowledge they have gained in the world of work.